Mucormycosis: An Emerging Fungal Infection in the COVID-19 Pandemic - Parisa Saberi-Hasanabadi1, 2; Milad Esmaeilzadeh Farmad3; Ramin Ataee4 (Journal of Medical Microbiology and Infectious Diseases)
During the COVID-19 pandemic, there has been a resurgence of mucormycosis, a rare and opportunistic fungal infection, with India reporting a particularly notable increase in incidence. Mucormycosis is a life-threatening condition that requires prompt diagnosis and treatment to prevent high mortality rates and severe sequelae. It is caused by the inhalation of spores from ubiquitous filamentous fungi belonging to the order Mucorales. Individuals with compromised immune systems or underlying conditions, such as diabetes, ketoacidosis, and neutropenia, are particularly vulnerable to infection. The risk and severity of mucormycosis are exacerbated by several factors, including corticosteroid therapy, prolonged intensive care stay, and the use of ventilators. Additionally, contaminated oxygen humidifiers pose a significant risk. Effective management of mucormycosis in critically ill COVID-19 patients relies on early diagnosis, optimization of predisposing factors, timely antifungal treatment, surgical debridement, and adjuvant therapies. Imaging modalities such as contrast-enhanced CT scans and MRI are crucial for guiding surgical debridement and assessing disease extent. This review article provides a comprehensive overview of the clinical pathogenesis, risk factors, diagnosis, treatment, and challenges associated with mucormycosis in COVID-19 patients, summarizing the latest findings in this field.